Identity-Based information Outsourcing with Comprehensive Auditing in Clouds: A Study - Raju, C. Anilkumar (International Journal of Computer Sciences and Engineering, 2025)
Cloud storage system provides helpful file storage and sharing services for distributed purchasers. to handle integrity, manageable outsourcing and origin auditing issues on outsourced files, we have a tendency to propose Associate in Nursing identity-based information outsourcing (IBDO) theme equipped with fascinating options advantageous over existing proposals in securing outsourced information. First, our IBDO theme permits a user to authorize dedicated proxies to transfer information to the cloud storage server on her behalf, e.g., an organization could authorize some staff to transfer files to the company’s cloud account in an exceedingly controlled means. The proxies area unit known and approved with their recognizable identities, that eliminates difficult certificate management in usual secure distributed computing systems. Second, our IBDO theme facilitates comprehensive auditing, i.e., our theme not solely permits regular integrity auditing as in existing schemes for securing outsourced information, however conjointly permits to audit the information|the knowledge|the information on data origin, kind and consistence of outsourced files. Security analysis and experimental analysis indicate that our IBDO theme provides robust security with fascinating potency.